The Impact Of The Curriculum Framework Of Pre- University Education In Literary Writing - Vehbi Miftari; Arbnore Mahaj (Association of Social and Educational Innovation, 2018)
The Curriculum Framework of Pre-University Education in the Republic of Kosovo has set the cultivation of personal identity, national and cultural affiliation as a fundamental goal (article 1.3.). So far, the education system is based on the promotion of personal and cultural identity of pupils. Beyond the provided qualitative education, through the curricular content the system aims to raise the awareness and the cultivation of these affiliations. Some basic learning competencies which provide the fulfillment of these affiliations have been clearly defined. One of them is the competence of communication and expression. Book content and teaching methodology can both significantly affect the interface between students' works and the stimulation of their imaginative creativity. One of these habits is artistic work. In this paper, we analyze the relation between the National Curriculum, especially its aims, competencies and areas, which are connected to the cultural identity, in one hand, and the content of books and teaching methods applied by teachers of the lower secondary schools (grades 6-9), on the other hand. After that, we analyze the impact of the curricula, book content and the teaching methods on the stimulation of students' imaginative creation. We found that only 10 percent of the book content is connected to the first goal of the Curriculum. The methodology often is not in harmony with the content, and no additional content is provided to cover this gap.